2021
DOI: 10.3390/ani11123466
|View full text |Cite
|
Sign up to set email alerts
|

Are We Approaching Peak Meat Consumption? Analysis of Meat Consumption from 2000 to 2019 in 35 Countries and Its Relationship to Gross Domestic Product

Abstract: Growing prosperity, but also disease outbreaks, natural disasters, and consumer preferences are changing global meat consumption. We investigated the 2000–2019 trends in 35 countries monitored by the Food and Agriculture Organization and the Organisation for Economic Co-operation and Development. We also tested relationships with Gross Domestic Product (GDP). Several countries appeared to be reaching peak consumption of some meats, and three (New Zealand, Canada, and Switzerland) have reached this. Poultry con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 17 publications
2
66
0
Order By: Relevance
“…According to the last Chilean dietary survey (2010) ( 33 ), the population had a median processed meat consumption of 26.4 g/day; intake among respondents with similar characteristics to our participants in terms of age, sex, region, and rurality, ranged from 19 to 32 g/day. However, these figures are 10 years old, and since then the consumption of animal protein has increased in Chile ( 51 ). In our study, more than 25% of participants consumed processed meat twice or more per week.…”
Section: Discussionmentioning
confidence: 99%
“…According to the last Chilean dietary survey (2010) ( 33 ), the population had a median processed meat consumption of 26.4 g/day; intake among respondents with similar characteristics to our participants in terms of age, sex, region, and rurality, ranged from 19 to 32 g/day. However, these figures are 10 years old, and since then the consumption of animal protein has increased in Chile ( 51 ). In our study, more than 25% of participants consumed processed meat twice or more per week.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 College of Life Science and Agriculture Forestry, Qiqihar University, Qiqihar 161006, Heilongjiang, China. 2 Department of Surgery of Spine and Spinal Cord, Henan Provincial People's Hospital, Zhengzhou 450003, Henan, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Poultry meat is the main source of nutritional protein that is consumed by humans worldwide [ 1 ]. As the European Union bans antibiotics as growth promoters and with the concerning spread of antibiotic resistance [ 2 ], alternative methods to prevent infection and maintain healthy chicken flocks are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…From a global perspective, meat consumption is also changing. An analysis of data from 35 countries between 2009 and 2019 showed that certain countries—New Zealand, Canada and Switzerland—are reaching a plateau of peak meat consumption [ 9 ]. In general, over these 35 countries, poultry consumption increased whilst that of beef and lamb/mutton declined [ 9 ].…”
Section: Introductionmentioning
confidence: 99%